Intercropping with wheat lowers nutrient uptake and biomass accumulation of maize, but increases photosynthetic rate of the ear leaf - Gou, Fang; van Ittersum, Martin K; Couëdel, Antoine; Zhang, Yue; Wang, Yajun; van der Putten, Peter E L; Zhang, Lizhen; van der Werf, Wopke (AoB plants, 2018)
Maize and wheat are globally important food crops. The two species can be grown as an intercrop, with substantial land sparing in the order of 20 %, as expressed by a land equivalent ratio of ~1.2. Here, we study nutrient uptake and the photosynthesis rate of intercropped maize and show that nutrient uptake is constrained by competition with wheat, while the photosynthesis rate is not decreased, but—surprisingly—increased. Ecophysiological mechanisms potentially underlying the unexpected high photosynthesis rate in intercropped maize are discussed. Abstract Intercropping is an ancient agricultural practice that provides a possible pathway for sustainable increases in crop yields. Here, we determine how competition with wheat affects nutrient uptake (nitrogen and phosphorus) and leaf traits, such as photosynthetic rate, in maize. In a field experiment, maize was planted as a sole crop, in three different intercrop configurations with wheat (a replacement intercrop and two add-row intercrops), and as a skip-row system with one out of each three maize rows omitted. Nitrogen and phosphorus uptake were determined at flowering and maturity. Specific leaf area, leaf nitrogen concentration, chlorophyll content and photosynthetic rate of the ear leaf were determined at flowering. Nitrogen and phosphorus concentrations were significantly lower in intercropped maize than in sole maize and skip-row maize at flowering, but these differences were smaller at maturity. At flowering, specific leaf area was significantly greater in intercrops than in skip-row maize. Leaf nitrogen concentration was significantly lower in add-row intercrops than in sole maize, skip-row maize or maize in the replacement intercrop. Leaf chlorophyll content was highest in sole and skip-row maize, intermediate in maize in the replacement intercrop and lowest in maize grown in add-row intercrops. On the contrary, photosynthetic rate was significantly higher in the replacement intercrop than in sole maize, skip-row maize and the intercrop with an additional maize row. The findings indicate that competition with intercropped wheat severely constrained nutrient uptake in maize, while photosynthetic rate of the ear leaf was not negatively affected. Possible mechanisms for higher photosynthesis rate at lower leaf nitrogen content in intercropped maize are discussed.